Genomics, physiology, and molecular breeding approaches for improving salt tolerance - Ismail, Abdelbagi M.; Horie, Tomoaki (Annual Reviews, 2017)
Salt stress reduces land and water productivity and contributes to poverty and food insecurity. Increased salinization caused by human practices and climate change is progressively reducing agriculture productivity despite escalating calls for more food. Plant responses to salt stress are well understood, involving numerous critical processes that are each controlled by multiple genes. Knowledge of the critical mechanisms controlling salt uptake and exclusion from functioning tissues, signaling of salt stress, and the arsenal of protective metabolites is advancing. However, little progress has been made in developing salt-tolerant varieties of crop species using standard (but slow) breeding approaches. The genetic diversity available within cultivated crops and their wild relatives provides rich sources for trait and gene discovery that has yet to be sufficiently utilized. Transforming this knowledge into modern approaches using genomics and molecular tools for precision breeding will accelerate the development of tolerant cultivars and help sustain food production.